Nacional-desenvolvimentismo e política externa brasileira : o pensamento político de San Tiago Dantas entre 1950 e 1960 - Ribeiro, Renato Ferreira (Universidade Federal de São Carlos, 2016)
This research intends to investigate the influence of ideological debate and therefore the internal political struggle in the formulation of Brazilian foreign policy during the democratic period of 1945-1964. It tests the hypothesis that the formulation and implementation of the Independent Foreign Policy, in the early 1960s years, corresponded to the radicalization of the national development project and was the culmination of a instrumentalization process of the foreign policy to the national project, started at least since the second government of Getúlio Vargas (1951-1954). Through the analysis of some documents and texts from Francisco Clementino de San Tiago Dantas, important Brazilian intellectual and politician, we intend to identify concepts, theories and arguments that characterize his political thought as well as its correspondence with the ideas that supported the foreign policy in the period 1950-1960.
National-developmentalism and brazilian foreign policy : the political thought of San Tiago Dantas between 1950 e 1960
Keywords: San Tiago Dantas; Política externa brasileira; Política externa para o desenvolvimento; National-developmentalism; Brazilian Foreign Policy; Foreign policy for development; Nacional-desenvolvimentismo; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICA INTERNACIONAL